Specialized Cranial Muscles: How Different Are They from Limb and Abdominal Muscles? - Sciote, James J. (2003)
Mammalian skeletal muscle fibers can be classified into functional types by the heavy chain (MyHC) and light chain (MyLC) isoforms of myosin (the primary motor protein) that they contain. Most human skeletal muscle contains fiber types and myosin isoforms I, IIA and IIX. Some highly specialized muscle fibers in human extraocular and jaw-closing muscles express either novel myosins or unusual combinations of isoforms of unknown functional significance. Extrinsic laryngeal muscles may express the extraocular MyHC isoform for rapid contraction and a tonic MyHC isoform for slow tonic contractions. In jaw-closing muscles, fiber phenotypes and myosin expression have been characterized as highly unusual. The jaw-closing muscles of most carnivores and primates have tissue-specific expression of the type IIM or `type II masticatory' MyHC. Human jaw-closing muscles, however, do not contain IIM myosin. Rather, they express myosins typical of developing or cardiac muscle in addition to type I, IIA and IIX myosins, and many of their fibers are hybrids, expressing two or more isoforms. Fiber morphology is also unusual in that the type II fibers are mostly of smaller diameter than type I. By combining physiological and biochemical techniques it is possible to determine the maximum velocity of unloaded shortening (V(o)) of an individual skeletal muscle fiber and subsequently determine the type and amount of myosin isoform. When analyzed, some laryngeal fibers shorten at much faster rates than type II fibers from limb and abdominal muscle. Yet some type I fibers in masseter show an opposite trend towards speeds 10-fold slower than type I fibers of limb muscle. These unusual shortening velocities are most probably regulated by MyHC isoforms in laryngeal fibers and by MyLC isoforms in masseter. For the jaw-closing muscles, this finding represents the first case in human muscle of physiological regulation of kinetics by light chains. To gether, these results demonstrate that, compared to other skeletal muscles, cranial muscles have a wider repertoire of contractile protein expression and function. Molecular techniques for reverse transcription of mRNA and amplification by polymerase chain reaction have been applied to typing of single fibers isolated from limb muscles, successfully identifying pure type I, IIA and IIX and hybrid type I/IIA and IIA/IIX fibers. This demonstrates the potential for future studies of the regulation of gene expression in jaw-closing and laryngeal muscles, which have such a variety of complex fiber types fitting them for their roles in vivo.